Intranasal dexmedetomidine and intranasal ketamine association allows shorter induction time for pediatric sedation compared to intranasal dexmedetomidine and oral midazolam - Francesca Cossovel; Andrea Trombetta; Augusto Ramondo; Guglielmo Riccio; Luca Ronfani; Alessia Saccari; Giorgio Cozzi; Egidio Barbi (BMC, 2022)
Abstract Background Non-painful diagnostic procedures require an inactive state for a prolonged time, so that sedation is often needed in younger children to perform the procedures. Our standard of care in this setting consists of the association between oral midazolam (0.5 mg/kg) and intranasal dexmedetomidine (4 mcg/kg). One of the limits of this approach is that the onset of action is quite delayed (up to 55 min) and poorly predictable. We chose to compare this association with intranasal-ketamine and intranasal-dexmedetomidine. Methods This is a "pre-post" study. The study population included the first forty children receiving sedation with the "new" combination intranasal ketamine (3 mg/kg) and intranasal dexmedetomidine (4 mcg/kg) compared to a historical cohort including the last forty children receiving sedation with our standard of care combination of intranasal dexmedetomidine (4mcg/kg) and oral midazolam (0,5 mg/kg). Results The association intranasal dexmedetomidine and intranasal ketamine allowed for a significantly shorter sedation induction time than the combination intranasal dexmedetomidine and oral midazolam (13,5 min versus 35 min). Both group's cumulative data showed a correlation between age and sedation effectiveness, with younger children presenting a higher success rate and shorter induction time (p 0,001). Conclusions: This study suggests that the ketamine and dexmedetomidine intranasal association may have a shorter onset of action when compared to intranasal dexmedetomidine and oral midazolam.